Tensor description of X-ray magnetic dichroism at the Fe L2,3-edges of Fe3O4 - Elnaggar, Hebatalla; Haverkort, Maurits W.; Hamed, M. H.; Dhesi, S. S.; de Groot, F. M. F. (Journal of synchrotron radiation, 2021)
A general description of magnetic dichroism effects in X-ray absorption spectroscopy using a few fundamental spectra extracted from experimental measurements is provided. The accuracy of the procedure is investigated theoretically.